Facilitating Vaginal Hysterectomy with Innovative Surgical Techniques - Mosley, Mary (MD Conference Express, 2014)
Vaginal hysterectomy (VH) is the most minimally invasive approach for hysterectomy in women with benign gynecologic disease. During the Donald F. Richardson Memorial Lecture, Rosann M. Kho, MD, formerly of the Mayo Clinic, Scottsdale, Arizona, USA, stated that it is time to transform the view of VH to increase its use and provide benefit to more women, most of whom would qualify for this approach. This requires defining new patient selection criteria while incorporating new surgical technologies, devices, and techniques to overcome the traditional challenges that have limited the use of VH.